Pembiasaan Cuci Tangan yang Baik dan Benar pada Siswa Taman Kanak-Kanak (TK) di Semarang - Rohmat Suprapto; Mardiyan Hayati; Silvia Nurbaity; Fitri Anggraeni; Satria Haritsatama; Tsamarah Qaulan Sadida; Almah Firoh; Flandita Alri Pratama (Jurnal Surya Masyarakat, 2020)
This study aims to provide counseling for kindergarten ABA 48 Semarang children to have healthy and clean hand washing. The method is done through (1) counseling / lecturing, (2) video learning, (3) hands-on practice. Respondents were 23 children. The results obtained 74.0% that children are not accustomed to washing hands according to health protocols and 26% that conforms to health standards. After counseling with three methods there was a change in knowledge and attitudes in washing hands, which from 26% increased to 56.5%. In conclusion, habituation to wash hands according to WHO standards can be successful if through three steps, a mirror, audio visual learning aids and direct practice with running water.